Do Macroeconomic Variables Influence Domestic Stock Market Price Behaviour in Emerging Markets? A Johansen Cointegration Approach to the Botswana Stock Market - Sikalao-Lekobane, Onneetse L. (Journal of Economics and Behavioral Studies, 2014)
The ability of the stock market to reflect real economic activities through fundamental macroeconomic variables in emerging markets remains paramount considering the role of stock markets in the financial system. This paper explores the long-term equilibrium relationship between the Botswana stock market price and selected domestic and global macroeconomic variables using quarterly data for the period 1998 to 2012. The selected macroeconomic variables included Gross Domestic Product (GDP), long and short-term interest rates, money supply, foreign reserves, inflation, diamond price index, exchange rate, US share price index and 10 Year US government bond yield. The paper employs VECM framework following Johansen’s cointegration technique. The analysis revealed that macroeconomic variables and the stock market price are cointegrated, hence, a long-run equilibrium relationship existed between them. The results showed that in the long run, real GDP, short-term interest rates, inflation and diamond index are positively related with stock market price. However, long-term real interest rate, money supply, foreign reserves, exchange rate, US share price index and US government bond yield are negatively related with stock market price in the long run.